2011
DOI: 10.1371/journal.pone.0020538
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillars and Fungal Pathogens: Two Co-Occurring Parasites of an Ant-Plant Mutualism

Abstract: In mutualisms, each interacting species obtains resources from its partner that it would obtain less efficiently if alone, and so derives a net fitness benefit. In exchange for shelter (domatia) and food, mutualistic plant-ants protect their host myrmecophytes from herbivores, encroaching vines and fungal pathogens. Although selective filters enable myrmecophytes to host those ant species most favorable to their fitness, some insects can by-pass these filters, exploiting the rewards supplied whilst providing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Additionally, there was reason to believe that two pairs of studies could have reported on the same species combinations. One of the combinations reported by González-Teuber and Heil (2010) could be identical to one of the combinations examined in Gonzalez-Teuber et al (2014) and, secondly, Roux et al (2011) and Belin-Depoux et al (1997) reported on identical plant-pathogen combinations with the only difference that one of two excluded ant species was different. If the common ant species was responsible for the observed effect, the two studies would have identical combinations.…”
Section: Ant Hygiene Extending To Plants Quantificationsmentioning
confidence: 67%
See 1 more Smart Citation
“…Additionally, there was reason to believe that two pairs of studies could have reported on the same species combinations. One of the combinations reported by González-Teuber and Heil (2010) could be identical to one of the combinations examined in Gonzalez-Teuber et al (2014) and, secondly, Roux et al (2011) and Belin-Depoux et al (1997) reported on identical plant-pathogen combinations with the only difference that one of two excluded ant species was different. If the common ant species was responsible for the observed effect, the two studies would have identical combinations.…”
Section: Ant Hygiene Extending To Plants Quantificationsmentioning
confidence: 67%
“…Another myrmecophyte, Cecropia obtuse, also showed reduced fungal infections when inhabited by its obligate ant partners Azteca alfari and A. ovaticeps (Roux et al 2011). Among treelets inhabited by Azteca ants, the percentage of plants infected by the fungi Fusarium moniliforme was more than five-fold lower than on un-inhabited plants.…”
Section: Ant-plant Systems With Pathogen Protectionmentioning
confidence: 99%
“…There can be several mechanisms behind pathogen protection. For example, ants may inhibit plant pathogens by eating fungal spores (Letourneau, 1998;Thornham et al, 2011), excreting antibiotics (Peng & Christian, 2005;Gonzalez-Teuber et al, 2014) or by deterring diseases vectors (Letourneau, 1998;Roux et al, 2011). Taken together, the provision of these three types of services may lead to highly effective ant-based biocontrol programs.…”
Section: Introductionmentioning
confidence: 99%
“…Prokaryotes include several kinds of microorganisms, such as archaea, bacteria, and cyanobacteria (7). Most such microorganisms do not normally cause disease in humans, existing either in a state of commensalism or in mutualism with the host (8)(9)(10). This nonharmful condition occurs when the immune system works well, but the same organisms can cause infection when the latter fails.…”
Section: Introductionmentioning
confidence: 99%